Neurological manifestations of coronavirus infections – a systematic review. Issue 10 (27th August 2020) - Almqvist, Jesper; Granberg, Tobias; Tzortzakakis, Antonios; Klironomos, Stefanos; Kollia, Evangelia; Öhberg, Claes; Martin, Roland; Piehl, Fredrik; Ouellette, Russell; Ineichen, Benjamin V.
Abstract: To optimize diagnostic workup of the current severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2) pandemic, we systematically reviewed neurological and neuroradiological manifestations of SARS‐CoV‐2 and all other known human coronavirus species (HCoV). Which lessons can we learn? We identified relevant publications (until 26 July 2020) using systematic searches in PubMed, Web of Science, and Ovid EMBASE with predefined search strings. A total of 4571 unique publications were retrieved, out of which 378 publications were selected for in‐depth analysis by two raters, including a total of 17549 (out of which were 14418 SARS‐CoV‐2) patients. Neurological complications and associated neuroradiological manifestations are prevalent for all HCoVs (HCoV‐229E, HKU1, NL63, OC43, Middle East respiratory syndrome (MERS)‐CoV, SARS‐CoV‐1, and SARS‐CoV‐2). Moreover there are similarities in symptomatology across different HCoVs, particularly between SARS‐CoV‐1 and SARS‐CoV‐2. Common neurological manifestations include fatigue, headache, and smell/taste disorders. Additionally, clinicians need to be attentive for at least five classes of neurological complications: (1) Cerebrovascular disorders including ischemic stroke and macro/micro‐hemorrhages, (2) encephalopathies, (3) para‐/postinfectious immune‐mediated complications such as Guillain‐Barré syndrome and acute disseminated encephalomyelitis, (4) (meningo‐)encephalitis, potentially with concomitant seizures, and (5) neuropsychiatric complications such as psychosis and mood disorders. Our systematic review highlights the need for vigilance regarding neurological complications in patients infected by SARS‐CoV‐2 and other HCoVs, especially since some complications may result in chronic disability. Neuroimaging protocols should be designed to specifically screen for these complications. Therefore, we propose practical imaging guidelines to facilitate the diagnostic workup and monitoring of patients infected with HCoVs.